Penerapan Pidana Terhadap Pelaku Penganiayaan Anak Ditinjau dari Prespektif UU Perlindungan Anak - fadrian, fadrian; wanda, wanda; kausar, kausar; iqbal, iqbal; martha, martha (Legalita, 2023)
Violence against children In many cases in Indonesia, a large part of the cause is a lack of awareness of child protection among parents or caregivers. Common types of violence are physical, emotional, sexual, and child neglect, all of which fall under the category of child abuse crimes. Therefore, there must be a legal basis to regulate child abuse in Indonesia to prevent the increase in cases. Some of the issues highlighted in this study include how laws and regulations regulate perpetrators of child abuse crimes in Indonesia and procedures for criminal sanctions against perpetrators of violence against children.